Genomic insights into pediatric intestinal inflammatory and eosinophilic disorders using single-cell RNA-sequencing - Keever-Keigher, Marissa R.; Harvey, Lisa; Williams, Veronica; Vyhlidal, Carrie A.; Ahmed, Atif A.; Johnston, Jeffery J.; Louiselle, Daniel A.; Grundberg, Elin; Pastinen, Tomi; Friesen, Craig A.; Chevalier, Rachel; Smail, Craig; et al. (Frontiers in Immunology, 2024)
Chronic inflammation of the gastrointestinal tissues underlies gastrointestinal inflammatory disorders, leading to tissue damage and a constellation of painful and debilitating symptoms. These disorders include inflammatory bowel diseases (Crohn's disease and ulcerative colitis), and eosinophilic disorders (eosinophilic esophagitis and eosinophilic duodenitis). Gastrointestinal inflammatory disorders can often present with overlapping symptoms necessitating the use of invasive procedures to give an accurate diagnosis. This study used peripheral blood mononuclear cells from individuals with Crohn's disease, ulcerative colitis, eosinophilic esophagitis, and eosinophilic duodenitis to better understand the alterations to the transcriptome of individuals with these diseases and identify potential markers of active inflammation within the peripheral blood of patients that may be useful in diagnosis. Single-cell RNA-sequencing was performed on peripheral blood mononuclear cells isolated from the blood samples of pediatric patients diagnosed with gastrointestinal disorders, including Crohn's disease, ulcerative colitis, eosinophilic esophagitis, eosinophilic duodenitis, and controls with histologically healthy gastrointestinal tracts. We identified 730 (FDR < 0.05) differentially expressed genes between individuals with gastrointestinal disorders and controls across eight immune cell types. There were common patterns among GI disorders, such as the widespread upregulation of MTRNR2L8 across cell types, and many differentially expressed genes showed distinct patterns of dysregulation among the different gastrointestinal diseases compared to controls, including upregulation of XIST across cell types among individuals with ulcerative colitis and upregulation of Th2-associated genes in eosinophilic disorders. These findings indicate both overlapping and distinct alterations to the transcriptome of individuals with gastrointestinal disorders compared to controls, which provide insight as to which genes may be useful as markers for disease in the peripheral blood of patients.